Cryptococcus gattii in an Immunocompetent Patient in the Southeastern United States - John W. Amburgy; Joseph H. Miller; Benjamin J. Ditty; Patrick Vande Lune; Shaaf Muhammad; Winfield S. Fisher (Case Reports in Infectious Diseases)
Cryptococcal infections are seen throughout the United States in both immunocompromised and immunocompetent patients. The most common form is C. neoformans. In the Northwestern United States, C. gattii has received considerable attention secondary to increased virulence resulting in significant morbidity and mortality. There are no cases in the extant literature describing a patient with C. gattii requiring neurosurgical intervention in Alabama. A middle-aged immunocompetent male with no recent travel or identifiable exposure presented with meningitis secondary to C. gattii. The patient underwent 12 lumbar punctures and a ventriculoperitoneal shunt and required 83 days of inpatient therapy with 5-flucytosine and amphotericin B. The patient was found to have multiple intracranial lesions and a large intramedullary spinal cryptococcoma within his conus. Following an almost 3-month hospitalization the patient required treatment with oral voriconazole for one year. In the United States meningitis caused by C. gattii infection is not isolated to the Northwestern region.